2021
DOI: 10.1111/mam.12275
|View full text |Cite
|
Sign up to set email alerts
|

A review of philopatry and dispersal in felids living in an anthropised world

Abstract: Typically, males of polygamous mammals are responsible for population connectivity and gene flow via dispersal, whereas females, showing stronger philopatry, strengthen local population stability and growth. These expectations can be disrupted by human disturbances; however, this possibility has been poorly examined in wide‐ranging mammals that are important targets for conservation. By reviewing philopatry and dispersal in felids, we aimed to evaluate: 1) whether the sex‐related patterns of philopatry and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 107 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…Anthropogenic disturbances have been found to disrupt this sex-related behavioral pattern and alter population dynamics in cougars and other felid species (Maehr et al, 2002;Stoner et al, 2013;de Oliveira et al, 2021). For example, Maehr et al (2002) reported all female cougars from the isolated Florida (USA) population to be philopatric, as expected.…”
Section: Introductionmentioning
confidence: 72%
“…Anthropogenic disturbances have been found to disrupt this sex-related behavioral pattern and alter population dynamics in cougars and other felid species (Maehr et al, 2002;Stoner et al, 2013;de Oliveira et al, 2021). For example, Maehr et al (2002) reported all female cougars from the isolated Florida (USA) population to be philopatric, as expected.…”
Section: Introductionmentioning
confidence: 72%
“…However, we cannot rule out that this topology is due to mitogenomic incomplete lineage sorting, as in leopards, males have higher dispersal than females. 43 On the other hand, the introgression between Arabian and Anatolian leopards is supported by the autosomal phylogeny, as the 100 Kbp sliding windows phylogeny clusters Arabian and one sample of Anatolian leopard together ( Figure S1 B). Their past continuous distribution through Northern Arabia could have helped in promoting gene flow between these two genetically and morphologically distinct subspecies.…”
Section: Discussionmentioning
confidence: 94%
“…On the one hand, the introgression between African and Arabian leopards is also partially supported by the mitochondrial phylogeny, as both groups cluster together, suggesting a possible migration corridor for females between Africa and the Arabian peninsula. However, we cannot rule out that this topology is due to mitogenomic incomplete lineage sorting, as in leopards males have higher dispersal than females (de Oliveira et al, 2022). On the other hand, the introgression between Arabian and Anatolian leopards is supported by the autosomal phylogeny, as the 100 Kbp sliding windows phylogeny clusters Arabian and one sample of Anatolian leopard together (Fig.…”
Section: Discussionmentioning
confidence: 97%